Rekomendasi Penerimaan Beasiswa Yayasan Untuk Siswa Baru SMK TI Airlangga dengan Algoritma C4.5 - Azahari Azahari; Nursobah Nursobah (STMIK Budi Darma, 2021)
The foundation scholarship path is a facility provided by the private sector to help government education programs realize 12 years of compulsory education, one of which is a three-year vocational high school education facility and of course the foundation will take into account who deserves three years of learning opportunities for students. Now this will help many parties who really deserve the opportunity to learn to foster their enthusiasm for learning again, but in this case also the foundation must certainly select candidates who apply for the scholarship, of course there are many who want to get the scholarship so that correct, accurate considerations must be made so that the scholarship does not fall into the wrong hands, one of the right ways is to classify the incoming data using the C4.5 algorithm application so that the canteen selection process does not It takes a very long time and based on research, the final result of the C4.5 algorithm will form a decision tree to simplify the process of reading the result data and it is hoped that this will help the foundation in the selection of foundation scholarship recipients for new students. and the results obtained are 57% nominated students have the opportunity to receive scholarships provided by SMK TI Arilangga.